Utilization for Non-Communicable Diseases Management in Southeast Asia - Kaulina, Farah Luthfi; Sukihananto, Sukihananto (Poltekkes Kemenkes Tanjung Karang, 2024)
Non-communicable diseases (NCDs) are still a morbidity and mortality problem in Southeast Asia. However, NCD in Southeast Asia still needs to be handled faster. WHO recommends the use of digital in treating NCDs in Southeast Asia. Therefore, this literature review study aims to describe how mHealth is utilized to overcome the problem of NCDs in Southeast Asian countries. The author collected articles using Google Scholar and Proquest, which were published in 2019-2023. The focus of the search was articles published in English-language Research Journals. Researchers used advanced search with the keywords NCD, Non-communicable diseases, mHealth, Mobile Health, Nursing, and Health Promotion. Keywords are combined using Boolean and/or the online database that the researcher chose. Articles that have been filtered are filtered again by selecting research locations in Southeast Asian countries. Ten articles obtained came from research in Southeast Asian countries Indonesia (n=4), Malaysia (n=1), Singapore (n=1), Vietnam (n=1), Thailand (1), Cambodia (n=1), Philippines (n=1). All articles discussed the use of mHealth for NCD management in their countries and aimed to determine the barriers (n=3), feasibility (n=1), effectiveness (n=2), impact (n=2), potential (n=1), perception (n=1), and perspective (n=1) of service providers, as well as the experience of using mHealth in remote areas (n=1). It can be concluded that mHealth can be used for independent screening for PTM, providing education about NCDs, and can be applied in rural areas as a comprehensive effort to handle NCDs.